TUBECTOMY TO PREVENT SUBSEQUENT CONCEPTION AND DYSTOCIA IN COWS AFFECTED WITH NARROW PELVIS - SATHIAMOORTHY, T; DEVANATHAN, T G; KULASEKAR, K; ASOKAN, S A; BALASUBRAMANIAN, S; RANGASAMY, S; RAJA, S (The Indian Journal of Animal Reproduction, 2011)
Tubectomy performed in two narrow pelvis affected cows to prevent subsequent conception and dystocia is presented.